Discovery Learning and High-Level Thinking Skills in Student Explanatory Text Writing - Kemala Ardillah Swanda; Suhartono Suhartono; Urip Zaenal Fanani; Anas Ahmadi; Darni Darni (Journal of Science and Education (JSE), 2025)
This study aims to describe the role of students' high-level thinking skills through the Discovery Learning learning model in improving explanatory text writing skills. Explanatory texts, which serve to explain phenomena logically and systematically, contribute to the development of students' critical and analytical mindsets. Through the Discovery Learning approach, students are directed to find cause-and-effect relationships independently, thereby increasing their cognitive involvement in understanding and writing explanatory texts. The study also highlights the importance of explicit learning strategies such as scaffolding, the use of text models, and reflective exercises to support writing skills. However, there are various challenges such as limited ability to organize ideas, lack of understanding of academic language, and low intrinsic motivation of students. The results of the study show that the implementation of the Discovery Learning learning model  has proven to be effective in improving skills in explanatory text writing because it encourages students to discover important concepts on their own through the process of active exploration. This study recommends the consistent integration of explanatory text-based approaches and Discovery Learning in educational practices to comprehensively improve students' academic literacy.